Incidental Gallbladder Carcinoma in Post Cholecystectomy Done for Suspected Benign Lesions at a Tertiary Care Hospital - Ghelani, Siddhartha Dineshbhai; Gadhvi, Yuvraj Halubhai; Dobariya, Dhrumi Dhanjibhai (Annals of Pathology and Laboratory Medicine, 2025)
Background: Incidental gallbladder carcinoma (IGBC) refers to gallbladder cancer which is not suspected clinically or radiologically and is detected for the first time on histopathological examination (HPE). The increasing trend of laparoscopic procedures has made cholecystectomies one of the most common surgical specimens received for histopathological evaluation. The concern whether routine histopathological examination is needed for all cholecystectomy specimens still remains debatable. Materials and Methods: This retrospective data analysis was carried out at C. U. Shah Medical College, Surendranagar, in the pathology department from January 2023 to December 2024 (2 Years), including 272 patients who have undergone cholecystectomy and sent gall bladder specimen for Histopathological examination in the pathology department. Results were analysed to find out the incidence of gall bladder carcinoma. Results: A total of 272 Cholecystectomy cases were received in the department over a period of 2 years. Out of 272 specimens, non-neoplastic lesions were 244, and 28 cases were of neoplastic etiology. Out of 28 cases, 20 cases were benign, and 8 cases (2.94%) were found malignant microscopically. Out of the eight cases of IGBC, 50% (4/8) were females while 50% (4/8) were males. The age group affected was 42-78 years (mean-62.5 years). Mean gall bladder wall thickness was 8.5 (±0.7) mm. Conclusion: In our study, we found the incidence of IGBC is 2.94%. Histopathological evaluation of all the routine cholecystectomy specimens is the gold standard for IGBC detection and is highly recommended irrespective of the radiological diagnosis or macroscopic findings.